Characterization and control of the causal agent of leaf spot in strawberry (Fragaria ananassa) under greenhouse conditions - Orellana, C. (2019)
Strawberry (Fragaria ananassa) plants showing symptoms of leaf spot were found in the producing areas of Manchay Bajo, Pachacamac District, Lima, Peru. The responsible pathogen was isolated and observed under a microscope to examine its morphological characteristics and the size of its structures, resulting in its identification as the fungus Corynespora cassiicola. Healthy strawberry plants that had been inoculated with C. cassiicola in a greenhouse developed lesions after 3 days and exhibited symptoms consisting of dark brown spots that had light brown centers and were surrounded by yellow halos, which coalesced and subsequently caused necrosis of the whole leaf. In vitro tests demonstrated that the fungus Trichoderma harzianum strain T-22 showed antagonistic activity against C. cassiicola, causing 41.8% mycelial growth inhibition, and the fungicides fosetyl-aluminum (Aliette®) and thiabendazole (Mertect®a) inhibited mycelial growth by 100.00% and 96.32%, respectively. However, in vivo, 0.75 g/L of the fungicide azoxystrobim (Stronsil®) gave the best control of C. cassiicola and the lowest area under the disease progress curve (AUDPC), followed by 1.5 mL/L of thiabendazole (Mertect) under greenhouse conditions. The isolate was found to be pathogenic, and its morphological identification was confirmed.